The effect of own and spousal parental leave on earnings - Elly-Ann Johansson (Institute for Labour Market Policy Evaluation (IFAU), 2010)
This paper investigates the effect of parental leave - both own and spousal - on subsequent earnings using different sources of variation. Using fixed-effect models, and in line with previous results, parental leave is found to decrease each parent's future earnings. Also spousal leave is important, but only for mothers. In fact, each month the father stays on parental leave has a larger positive effect on maternal earnings than a similar reduction in the mother's own leave. Using two reforms of the parental leave system as exogenous sources of variation yields only imprecisely estimated effects, even though the reforms had a strong effect on parental leave usage. However, the point estimates tentatively suggest effects in the same range or larger than the fixed-effects model found. - Parental leave ; gender equality ; earnings
Keywords: J13; J16; J24; 330; Elternzeit; Lohndifferenzierung; Geschlechterdiskriminierung; Schweden